Problematika Kepailitan Transnasional Terhadap Pengurusan dan Pemberesan Aset Debitur Pailit - Zakia Fhadillah; Ni Made Yordha Ayu Astiti; Mochamad Cholil; Muhammad Amirul Alfan; Maghfirah Aliefia (Fakultas Hukum Universitas Airlangga, 2023)
AbstractDecisions regarding bankruptcy issued by the Indonesian Commercial Court have several legal consequences. One of the legal consequences that arises is regarding the legal authority of the debtor to be able to manage his assets. Since the bankruptcy decision, the debtor’s assets will be subject to general confiscation. However, in implementing the bankruptcy decision, managing the assets of a bankrupt debtor is not as easy as one might imagine. Therefore, this article was created to analyze problems regarding the implementation of bankruptcy decisions such as the authority of foreign courts where the bankrupt debtor’s assets are located to be able to confiscate and auction off the debtor’s assets abroad if the debtor is declared bankrupt by the Indonesian Commercial Court. As well as regarding the status of the curator appointed by the Indonesian Commercial Court. The research in this article is legal research. This research uses statutory approach (statute approach), comparative approach (comparative approach), and conceptual approach (conceptual approach). The results of this study indicate that the implementation of bankruptcy decisions from the Indonesian Commercial Court cannot be executed immediately for the management and settlement of bankrupt debtor assets by the curator. So that finally raises a question about the status of the curator appointed by the Indonesian Commercial Court.Keywords: Bankruptcy; Transnational Bankruptcy; Debtor Assets. AbstrakPutusan pailit Pengadilan Niaga Indonesia memiliki beberapa akibat hukum. Salah satu akibat hukum yang ditimbulkannya berkaitan dengan kemampuan hukum debitur untuk menguasai harta kekayaannya. Harta debitur pada umumnya akan disita sebagai akibat putusan pailit. Namun, mengelola aset debitur pailit setelah keputusan pailit dibuat lebih sulit dari yang diperkirakan. Tujuan artikel ini adalah untuk membahas masalah pelaksanaan putusan pailit, seperti kewenangan pengadilan asing untuk menyita dan menjual aset debitur pailit di luar Indonesia. Juga mengenai status kurator yang diangkat oleh Pengadilan Niaga Indonesia. Penelitian dalam artikel ini adalah penelitian hukum. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan perundang-undangan (statute approach), pendekatan komparatif (comparative approach), dan pendekatan konseptual (conceptual approach). Hasil akhir dari penelitian ini menyatakan bahwasanya pelaksanaan putusan pailit dari Pengadilan Niaga Indonesia tidak bisa untuk dapat segera dilaksanakan mengenai pengurusan dan penyelesaian harta kekayaan debitur pailit oleh kurator. Sehingga akhirnya menimbulkan pertanyaan tentang status dari kurator yang diangkat oleh Pengadilan Niaga Indonesia.Kata Kunci: Pailit; Kepailitan Transnasional; Aset Debitur.